2015
DOI: 10.1039/c4tx00113c
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic alterations induced by Monuron in rat and human renal proximal tubule cells in vitro and comparison to rat renal-cortex in vivo

Abstract: -dimethyl-3-(4-chlorophenyl)urea) is a non-selective phenylurea herbicide, widely used in developing countries although concerns have been raised about its toxicity and carcinogenicity. Monuron was evaluated by the National Toxicology Program in 1988 and shown to be a male rat-specific renal carcinogen. We report that oral administration of Monuron to male rats for 3 days, leads to a larger number of genes being differentially expressed in the renal-cortex than in the liver. Further, we observed up-regulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Monuron is a phenylurea herbicide and a known renal carcinogen in rats as it has been shown to cause adenomas of the kidney and carcinomas of the liver [41]. In a study by Block et al they showed that monuron induced an upregulation of genes involved in cell cycle and cell proliferation in the renal cortex [42]. Due to its unclear mechanism of carcinogenicity a number of studies have classified it as a non-genotoxic renal carcinogen [43].…”
Section: Non-genotoxic Carcinogensmentioning
confidence: 99%
“…Monuron is a phenylurea herbicide and a known renal carcinogen in rats as it has been shown to cause adenomas of the kidney and carcinomas of the liver [41]. In a study by Block et al they showed that monuron induced an upregulation of genes involved in cell cycle and cell proliferation in the renal cortex [42]. Due to its unclear mechanism of carcinogenicity a number of studies have classified it as a non-genotoxic renal carcinogen [43].…”
Section: Non-genotoxic Carcinogensmentioning
confidence: 99%
“…Concerns have also been raised about monuron toxicity and carcinogenicity. It has been shown to induce chronic renal toxicity [ 17 ] and transcriptomic alteration [ 18 ] in rats, while its potential endocrine-disrupting effects [ 19 ] have been reported through in vitro studies. Chlorpropham, instead, has been linked to potentially adverse effects on human health in the long term, although the likelihood of exposure to it seems low.…”
Section: Introductionmentioning
confidence: 99%